Antioxidant and anti-inflammatory activities contribute to the prophylactic effect of semi-purified fractions obtained from the crude methanol extract of Muntingia calabura leaves against gastric ulceration in rats - Balana, Tavamani; Mohd Sani, Mohd. Hijaz; Mumtaz Ahmada, Salahuddin; Mohtarrudin, Norhafizah; Zakaria, Zainul Amiruddin (Elsevier, 2015)
Ethnopharmacological relevance In traditional medicine, the leaves, flowers, barks and roots of Muntingia calabura L. (Muntingiaceae) have been employed as a treatment for various ailments including dyspepsia and to relieve pain caused by gastritis and peptic ulcer disease. The methanolic extract of Muntingia calabura leaves (MEMC) has been proven in the previous study to possess significant antiulcer activity. In this study, we attempted to determine the prophylactic effect of the fractions obtained from MEMC against ethanol-induced gastric lesion in rats and the involvement of antioxidants and anti-inflammatory mediators.